Silencing of KIF3B Suppresses Breast Cancer Progression by Regulating EMT and Wnt/β-Catenin Signaling - Wang, Chengqin; Zhang, Runze; Wang, Xiao; Zheng, Yan; Jia, Huiqing; Li, Haiyan; Wang, Jin; Wang, Ning; Xiang, Fenggang; Li, Yujun (Frontiers in Oncology, 2021)
Breast cancer is the most common malignant tumors in women. Kinesin family member 3B (KIF3B) is a critical regulator in mitotic progression. The objective of this study was to explore the expression, regulation, and mechanism of KIF3B in 103 cases of breast cancer tissues, 35 metastatic lymph nodes and breast cancer cell lines, including MDA-MB-231, MDA-MB-453, T47D, and MCF-7. The results showed that KIF3B expression was up-regulated in breast cancer tissues and cell lines, and the expression level was correlated with tumor recurrence and lymph node metastasis, while knockdown of KIF3B suppressed cell proliferation, migration, and invasion both in vivo and in vitro. In addition, UALCAN analysis showed that KIF3B expression in breast cancer is increased, and the high expression of KIF3B in breast cancer is associated with poor prognosis. Furthermore, we found that silencing of KIF3B decreased the expression of Dvl2, phospho-GSK-3β, total and nucleus β-catenin, then subsequent down-regulation of Wnt/β-catenin signaling target genes such as CyclinD1, C-myc, MMP-2, MMP-7 and MMP-9 in breast cancer cells. In addition, KIF3B depletion inhibited epithelial mesenchymal transition (EMT) in breast cancer cells. Taken together, our results revealed that KIF3B is up-regulated in breast cancer which is potentially involved in breast cancer progression and metastasis. Silencing KIF3B might suppress the Wnt/β-catenin signaling pathway and EMT in breast cancer cells.